2022
DOI: 10.1136/annrheumdis-2022-eular.41
|View full text |Cite
|
Sign up to set email alerts
|

Ab0752 how Does Time to Diagnosis and Gender Affect Treatment Outcomes in Patients With Ankylosing Spondylitis or Psoriatic Arthritis? – Real World Data From the German Aquila Study With Secukinumab

Abstract: BackgroundIn both, ankylosing spondylitis (AS) and psoriatic arthritis (PsA), women typically have a longer delay in diagnosis.1,2 There is scientific evidence that prognosis for AS and PsA improves when diagnosed early. The German non-interventional study AQUILA provides real-world data on the influence of time to diagnosis and gender on treatment outcomes under secukinumab, a fully human monoclonal antibody that selectively inhibits interleukin-17A.ObjectivesThe aims of this interim analysis are to describe … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…Ramonda and colleagues also demonstrated a clear improvement in TJC and SJC after 6 months of treatment that was maintained for up to 24 months ( 46 ). In addition, comparable data were obtained in the observational prospective study AQUILA ( N = 1,145), which also showed that the efficacy of secukinumab in improving TJC/SJC was similar in males and females ( 48 ).…”
Section: Discussionsupporting
confidence: 69%
“…Ramonda and colleagues also demonstrated a clear improvement in TJC and SJC after 6 months of treatment that was maintained for up to 24 months ( 46 ). In addition, comparable data were obtained in the observational prospective study AQUILA ( N = 1,145), which also showed that the efficacy of secukinumab in improving TJC/SJC was similar in males and females ( 48 ).…”
Section: Discussionsupporting
confidence: 69%